ENHANCING STUDENTS’ CRITICAL THINKING SKILLS IN WRITING NARRATIVE THROUGH PEER-FEEDBACKING ACTIVITIES - Ade Fatimah Salafia (Journal of English Education Program (JEEP), 2021)
This study aims to find out whether peer-feedbacking activities effective in improving students’ critical thinking skills in writing narrative or not and students' perceptions on the use of peer-feedbacking in improving students’ critical thinking skills in writing narrative. This study applied a mixed method design which employed true-experimental with the type of pre-test post-test control group design for the quantitative data and close-ended questionnaire for the qualitative data. The population of this study were all students of tenth grade in one of vocational high school in Padaherang and the sample were 30 students as the experimental group and 30 students as the control group. The data of this study were obtained from pre-test, post-test and questionnaire. The result obtained from the pre-test and post-test concluded that Peer Feedback Activities is effective in teaching writing. The findings showed that the students’ score improved from pretest to posttest. In conclusion, there was a significant difference in students' critical thinking before and after being taught by means applying Peer Feedback Activities. Based on the questionnaire, the study concluded that the students expressed positive perceptions about peer feedback activities and it was effective in enhancing critical thinking in writing narrative. The future researchers  are suggested to conduct  experiment  or  action  research  to  improve  writing or  other dependent  variables   ability  through  peer -feedbacking.Keywords: Critical Thinking, Writing, Narrative, Peer Feedback.